2015
DOI: 10.4103/1817-1737.151439
|View full text |Cite
|
Sign up to set email alerts
|

The association between glucose levels and hospital outcomes in patients with acute exacerbations of chronic obstructive pulmonary disease

Abstract: BACKGROUND:Corticosteroids used for chronic obstructive pulmonary disease (COPD) exacerbations can cause hyperglycemia in hospitalized patients, and hyperglycemia may be associated with increased mortality, length of stay (LOS), and re-admissions in these patients.MATERIALS AND METHODS:We did three retrospective studies using charts from July 2008 through June 2009, January 2006 through December 2010, and October 2010 through March 2011. We collected demographic and clinical information, laboratory results, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…demonstrated that the highest glucose value during the first 24 h after ICU admission did not predict hospital mortality in the medical ICU 59 . Patients with chronic obstructive lung diseases treated with corticosteroids developed significant hyperglycemia, but the increase in blood glucose levels did not correlate with the maximum dose of corticosteroids and were not associated with mortality, length of hospital stay, or re-admission rates 60 . The duration of hyperglycemia or the amount of insulin given did not have a major impact on the outcome of patients with primary acute neuromuscular respiratory failure 61 .…”
Section: Discussionmentioning
confidence: 88%
“…demonstrated that the highest glucose value during the first 24 h after ICU admission did not predict hospital mortality in the medical ICU 59 . Patients with chronic obstructive lung diseases treated with corticosteroids developed significant hyperglycemia, but the increase in blood glucose levels did not correlate with the maximum dose of corticosteroids and were not associated with mortality, length of hospital stay, or re-admission rates 60 . The duration of hyperglycemia or the amount of insulin given did not have a major impact on the outcome of patients with primary acute neuromuscular respiratory failure 61 .…”
Section: Discussionmentioning
confidence: 88%
“… 25 In addition, among patients with chronic obstructive lung disease treated with corticosteroids who developed significant hyperglycemia, the increase in blood glucose levels did not correlate with the maximum corticosteroid dose, mortality, length of hospital stay, or readmission rates. 26 Moreover, neither the duration of hyperglycemia nor the amount of insulin administered affects the outcomes of patients with primary neuromuscular ARF. 27 …”
Section: Discussionmentioning
confidence: 99%
“…While blood glucose levels are not related to mortality, hospital stay duration, or re-hospitalization in patients with AECOPD, 28 detection of glucose in bronchoalveolar aspirate is associated with the presence of pathogenic bacteria. 29,30 In the present study, if bacteria were isolated in patients with AECOPD, BA-Glu levels were 1.8 times lower than those in patients without bacterial isolation, while no difference was found in S-Glu levels.…”
Section: Discussionmentioning
confidence: 87%